APPLICATION OF QUANTUM CHEMICAL, NOISE AND THE ELECTROCHEMICAL FREQUENCY MODULATION TO INVESTIGATE THE ADSORPTION AND CORROSION INHIBITION BEHAVIOR OF 2-AMINO-6-HYDROXYBENZOTHIAZOLE FOR STEEL API X80 IN ACIDIC SOLUTION - Danaee,I. (Sociedad Chilena de Química, 2020)
ABSTRACT Different theoretical, electrochemical and surface techniques were applied to study the corrosion inhibition effects of 2-Amino-6-hydroxybenzothiazole in 5% HCl solution. The density functional theory was carried out and quantum chemical factors like the energy gap, energy of highest occupied molecular orbital, the energy of lowest unoccupied molecular orbital, the fraction of electron transferred, and Mulliken charges have been calculated. In addition, according to quantum calculation, S atom in 2-Amino-6-hydroxybenzothiazole indicated more tendency for electrophilic attack in adsorption. The main reason for high inhibition efficiencies in very low concentrations is the planar and simplicity of inhibitor structure which leads to increasing the efficiency of adsorption by functional group especially sulfur. Electrochemical frequency modulation and potentiodynamic polarization indicated that this material has excellent inhibiting features in very low concentrations. The influence of DC trend on the explanation of electrochemical noise data was evaluated by polynomial fitting and the optimum polynomial order m=4 was obtained. Noise resistance and the inhibition efficiency was calculated and compared in different methods. The theory of shot noise in frequency domain was used to obtain the electrochemical event charge. The corroded surface of steel in the absence and existence of thiazole compound was studied by Atomic force microscopy.